SOCIO-ECONOMIC CONSEQUENCES OF UNEMPLOYMENT AND EFFECTIVE MECHANISMS FOR ITS REDUCTION - Kulmurotov, Sokhibjon Jumaniyozovich; Sayimova, Nilufar Hamidulla qizi (THE INNOVATION ECONOMY, 2026)
This article analyzes the impact of unemployment on socio-economic development. It scientifically substantiates that a high level of unemployment leads to a decline in living standards, a reduction in production volumes, and a disruption of social stability. In addition, the importance of state policy, the development of entrepreneurship, and the vocational training system in increasing employment and reducing unemployment is highlighted. The research findings have scientific and practical significance for improving employment policy and developing effective strategies.